The rise of the European consolidation state - Wolfgang Streeck (Max Planck Institute for the Study of Societies, 2015)
The rise of the consolidation state follows the displacement of the classical tax state, or Steuerstaat, by what I have called the debt state, a process that began in the 1980s in all rich capitalist democracies. Consolidation is the contemporary response to the "fiscal crisis of the state" envisaged as early as the late 1960s, when postwar growth had come to an end. Both the long-term increase in public debt and the current global attempts to bring it under control were intertwined with the "financialization" of advanced capitalism and its complex functions and dysfunctions. The ongoing shift towards a consolidation state involves a deep rebuilding of the political institutions of postwar democratic capitalism and its international order. This is the case in particular in Europe where consolidation coincides with an unprecedented increase in the scale of political rule under European Monetary Union and with the transformation of the latter into an asymmetric fiscal stabilization regime. The paper focuses on the developing structure of the new consolidation regime and its consequences for the relationship between capitalism and democracy. – – Der Aufstieg des Konsolidierungsstaats in Europa folgt der Ablösung des klassischen Steuerstaats durch den Schuldenstaat, ein Prozess, der in den 1980er-Jahren in allen reichen kapitalistischen Demokratien einsetzte. Konsolidierung ist die Antwort auf die schon in den späten 1960er-Jahren, als die Epoche des Nachkriegswachstums zu Ende ging, erwartete "Krise des Steuerstaats". Sowohl der langfristige Anstieg der Staatsverschuldung als auch die gegenwärtigen weltweiten Versuche, ihn rückgängig zu machen, sind mit der "Finanzialisierung" des entwickelten Kapitalismus und ihren komplexen Funktionen und Dysfunktionen auf das Engste verbunden. Der gegenwärtige Übergang zu einem Konsolidierungsstaat beinhaltet einen tiefgreifenden Umbau der politischen Institutionen des demokratischen Kapitalismus der Nachkriegszeit und seiner internationalen Ordnung. Dies gilt insbesondere für Europa, wo die fiskalische Konsolidierung mit einem beispiellosen Zuwachs in der Reichweite politischer Herrschaft in Gestalt der Europäischen Währungsunion und mit deren Transformation in ein asymmetrisches Regime fiskalischer Stabilisierung zusammenfällt. Das vorliegende Papier untersucht die sich herausbildende Struktur des neuen Konsolidierungsregimes und ihre Auswirkungen auf das Verhältnis von Kapitalismus und Demokratie.
Keywords: 300